Respon Tanaman Kedelai Terhadap Khelat Tembaga (Cu-edta) pada Tanah Gambut - Zulfatri '; Murniati ' (Universitas Riau, 2005)
An experiment was conducted to determine the effect of Cu-EDTA on the growth and production of soy heancultivated on peat soil. A completely randomized design was assigned with 6 treatments namely 0,50,1 (M),150,200 and 250 ppm of Cu-EDTA solution. It was found that application of Cu-EDl A increased .significantlythe primary branch, dry-matter, pi>d, percentage of fullyfilledpod, weight of .seeds and of H ) seeds/plant. ItMwas also found that treatment of 2(X) ppm of Cu-EDTA solution gave the highe.st value at most observations.